Genetic deletion in uncoupling protein 3 augments (18)F-fluorodeoxyglucose cardiac uptake in the ischemic heart - Gargiulo, Sara (BioMed Central, 2014)
BACKGROUND: We investigated the effects of uncoupling protein 3 (UCP3) genetic deletion on (18)F-fluorodeoxyglucose (FDG) cardiac uptake by positron emission tomography (PET)/computed tomography (CT) dedicated animal system after permanent coronary artery ligation. METHODS: Cardiac (18)F-FDG PET/CT was performed in UCP3 knockout (UCP3(−/−)) and wild-type (WT) mice one week after induction of myocardial infarction or sham procedure. RESULTS: In sham-operated mice no difference in left ventricular (LV) volume was detectable between WT and UCP3(−/−). After myocardial infarction, LV volume was higher in both WT and UCP3(−/−) compared to sham animals, with a significant interaction (p < 0.05) between genotype and myocardial infarction. In sham-operated animals no difference in FDG standardized uptake value (SUV) was detectable between WT (1.8 ± 0.6) and UCP3(−/−) (1.8 ± 0.6). After myocardial infarction SUV was significantly higher in remote areas than in infarcted territories in both UCP3−/− and WT mice (both p < 0.01). Moreover, in remote areas, SUV was significantly higher (p < 0.001) in UCP3−/− as compared to WT, while in the infarcted territory SUV was comparable (p = 0.29). A significant relationship (r = 0.68, p < 0.001) between LV volume and SUV was found. CONCLUSIONS: In a mice model of permanent coronary occlusion, UCP3 deficiency results in a metabolic shift that favored glycolytic metabolism and increased FDG uptake in remote areas.